The Sustainability of Wolverine Trapping Mortality in Southern Canada. Issue 2 (19th November 2019) - Mowat, Garth; Clevenger, Anthony P.; Kortello, Andrea D.; Hausleitner, Doris; Barrueto, Mirjam; Smit, Laura; Lamb, Clayton; DorsEy, BenJAMIN; Ott, Peter K.
Abstract : Current levels of trapping mortality are a threat to the wolverine population in southern Canada. Trapping kill should to be reduced to ≤4% to allow the population to increase in density and distribution. ABSTRACT: Range declines, habitat connectivity, and trapping have created conservation concern for wolverines throughout their range in North America. Previous researchers used population models and observed estimates of survival and reproduction to infer that current trapping rates limit population growth, except perhaps in the far north where trapping rates are lower. Assessing the sustainability of trapping requires demographic and abundance data that are expensive to acquire and are therefore usually only achievable for small populations, which makes generalization risky. We surveyed wolverines over a large area of southern British Columbia and Alberta, Canada, used spatial capture‐recapture models to estimate density, and calculated trapping kill rates using provincial fur harvest data. Wolverine density averaged 2 wolverines/1, 000 km 2 and was positively related to spring snow cover and negatively related to road density. Observed annual trapping mortality was >8.4%/year. This level of mortality is unlikely to be sustainable except in rare cases where movement rates are high among sub‐populations and sizable un‐trapped refuges exist. Our results suggest wolverine trapping is not sustainable because our study area was fragmented by human and natural barriers and few large refuges existed. We recommend future wolverine trapping mortality be reduced by ≥50% throughout southern British Columbia and Alberta to promote population recovery. © 2019 The Authors. The Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society.